Sistem Pengelolaan Keamanan Penerbangan Untuk Mendukung Rencana Peningkatan Status Bandar Udara Menjadi Bandar Udara Internasional (Studi Kasus di Bandar Udara Abdulrachman Saleh – Malang) - Zulaichah Zulaichah; Faridha Nahar (Research and Development Agency of The Ministry of Transportation, 2013)
Aviation security is important part of airport operation. Secure airport reflects the airport with good management. The Goverment of East Java Province plans to increase the status of Abdulrachman Saleh Airport from domestic airport to international airport. This policy must be supported by good aviation security. This research aims to find problems in the securitymanagement system and give policy recomendation about increasing the quality of aviation security in Abdulrachman Saleh Airport. The method in this research is SWOT analysis. This research will combine strenghs, weakness, opportunities and threats in Abdulrachman Saleh Airport. Based on research, there are 7(seven) policy recomendation which can increase the quality of aviation security. The recomendation are reconsideration about the organization which responsible for aviation security at Abdulrachman Saleh Airport, giving aviation security education and excellent services education for security personnel, increasing the height of security fence based on document ICAO doc.8973, location separation for passenger inspection and air cargo inspection, separation point for body search room and nursery room, making standard operational and procedure for motor vehicles inspection, and building motor vehicles checkpoint. Pemerintah Provinsi Jawa Timur Berencana akan meningkatkan status Bandar Udara Abdulrachman Saleh dari bandar udara domestik menjadi bandar udara internasional. Kebijakan ini tentunya harus didukung denan kualitas keamanan penerbangan yang baik. Penelitian ini bertujuan untuk mengetahui kendala dalam pengelolaan sistem keamanan dan memberikan rekomendasi kebijakan untuk peningkatan kualitas keamanan penerbangan di Bandar Udara Abdulrachman Saleh. Metode yang digunakan dalam penelitian ini adalah analisis SWOT. Berdasarkan hasil pengkajian, ada 7 (tujuh) rekomendasi kebijakan antara lain; Peninjauan kembali mengenai penanggung jawab keamanan penerbangan di Bandar Udara Abdulrachman Saleh, pemberian pendidikan terkait keamanan penerbangan dan pelayanan prima bagi personel keamanan, peningkatan tinggi pagar pembatas bandar udara sesuai dengan document ICAO doc 8973, pemisahan area pemeriksaan penumpang dan kargo udara, pemisahan antara ruang pemeriksaan fisik penumpang tertutup dan ruang menyusui, pembuatan SOP pemeriksaan kendaraan bermotor, dan pendirian pos pemeriksaan kendaraan bermotor.